Monographs in Sci-Tech Libraries, 1st edition - Mount, Ellis (Routledge, 2020)
This book, first published in 1983, is devoted to a consideration of the contributions monographs make to all types of sci-tech libraries as well as their probable role in the future. Several related topics are also included, such as sources for obtaining monographs, tools used for selecting them and the attitude of publishers towards their creation.